Are workers compensated by cheaper housing in regions where unemployment is high? Theory and evidence from a housing demand survey - Wouter Vermeulen; Jos Van Ommeren (European Regional Science Association (ERSA), 2005)
The empirical wage curve literature has demonstrated that workers in high-unemployment regions earn less. At the same time, many labour markets, especially in Europe, are characterised by persistent regional unemployment differentials and a low interregional labour mobility rate. It is argued in this paper that workers in high-unemployment regions are compensated in the housing market, which discourages migration to low-unemployment regions. We derive a multiregional efficiency wage model allowing for endogenous land prices, and therefore house prices, as well as endogenous lot sizes. It is shown that in high-unemployment regions, land prices are lower and lot sizes are larger. Therefore, aggregate regional house price data misrepresent the compensating differential. Employing a Dutch housing demand survey, we show that attribute corrected house prices and rents are 10.4 respectively 2.4 percent lower when regional unemployment is one percent higher.
Keywords: 330